(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
McCune-Albright syndrome (MAS) is an extremely rare disorder that classically affects the bones, skin and endocrine system. Classical features are fibrous dysplasia of bone, skin pigmentation and dysfunction of certain endocrine glands. Diagnosis of MAS is usually established on clinical grounds. Different imaging modalities help to confirm the fibrous dysplasia, among those radio iso-tope bone scan is an excellent tool for early diagnosis and evaluation of bony extension. Bangladesh J. Nuclear Med. 19(1): 61-63, January 2016